Marketing Strategy for Bottled Water (AMDK) CV Tirta Sasmita Pamulang - Rianto, Eko; Yuliyanto, Nur Alim; Mulyani, Sri Aan; Waliyati (Asian Journal of Management Analytics, 2023)
The title of this research is CV Tirta Sasmita Pamulang's bottled water marketing strategy (AMDK). This study aims to find out how the marketing strategy implemented by CV Tirta Sasmita Pamulang increased sales. The data used in this study are qualitative and quantitative. The sources of data used are primary and secondary. The methods used in collecting the required data are observation, Interview, documentation, and Literature Study. To find out how the strategy is used SWOT Analysis Method (Strength, Weakness, Opportunity, and Threat) From the results of the SWOT analysis, it was found that the position of the CV Tirta Sasmita bottled water business has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this situation is to support an aggressive growth policy.